2004
DOI: 10.5144/0256-4947.2004.259
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium decreases cardiac injury in patients undergoing coronary artery bypass surgery

Abstract: BackgroundThe calcium-channel blocking effect of magnesium might have protective effects in patients undergoing cardiopulmonary bypass surgery. We assessed the effects of magnesium on hearts undergoing coronary artery bypass surgery with intermittent warm blood hyperkalemic cardioplegia in the antegrade fashion.Patients and MethodsTwenty patients undergoing coronary bypass surgery were randomly divided into two groups, a control group who received intermittent antegrade warm blood hyperkalemic cardioplegia for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…Several of the included studies were characterized by a lack of information about allocation concealment ( n = 1) or blinding of outcome assessment ( n = 2). However, one study had a moderate risk of bias [ 27 ] and other evaluated studies had a low risk of bias according to selective outcome reporting. Details of the quality of bias assessment are shown in Table II .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several of the included studies were characterized by a lack of information about allocation concealment ( n = 1) or blinding of outcome assessment ( n = 2). However, one study had a moderate risk of bias [ 27 ] and other evaluated studies had a low risk of bias according to selective outcome reporting. Details of the quality of bias assessment are shown in Table II .…”
Section: Resultsmentioning
confidence: 99%
“…Participants in one study were only female [ 30 ], while the proportion of females in five studies ranged from 29% [ 8 ] to 78% [ 29 ]. In two studies the percentage of women was unknown [ 27 , 31 ]. The mean age of participants ranged from 18 [ 31 ] to 85 years [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have found that the enrichment of blood with magnesium improves hospital outcomes, 2 reduces new-onset postoperative atrial fibrillation, [3][4][5][6] and reduces the release of postoperative cardiac enzymes. [4][5][6][7] However, a retrospective study found comparable outcomes in an elderly population, 8 and other studies have shown that magnesium administration is harmful to patients with a left ventricular ejection fraction below 40%, 9 renal dysfunction, 10 or a tendency to bleed. 11 A Cochrane review of intravenous magnesium administration after acute myocardial infarction demonstrated that this practice was unlikely to reduce ischemic reperfusion injury.…”
mentioning
confidence: 99%